Development of a Web-Based Educational Management System for a Technology Vocational High School in Banda Aceh, Indonesia - Idroes, Rinaldi; Afidh, Razief Perucha Fauzie; Zahriah, Zahriah; Noviandy, Teuku Rizky; Sugara, Dimas Rendy; Ahsya, Yahdina; Amirah, Kelsy; Baihaqi, Baihaqi; Dharma, Aditia (Heca Sentra Analitika, 2024)
This study explores developing and implementing a web-based Management Information System (MIS) tailored for SMK Negeri 2 Banda Aceh, a vocational school in Indonesia. To enhance administrative efficiency and address unique challenges in vocational education, the system centralizes tasks such as attendance tracking, academic record management, and internship coordination. Employing the waterfall model, this project proceeded through structured phases, including requirements analysis, system design, development, and usability testing. A sample of 50 users, comprising students, teachers, and school operators, evaluated the system based on usability, interface design, and information clarity through a questionnaire, yielding high satisfaction scores. Reliability testing and correlation analysis revealed strong internal consistency across questionnaire items and identified critical factors influencing user satisfaction, such as interface appeal and effective error resolution. The results indicate that the system meets core user needs and contributes to a streamlined, user-friendly school management process. With implementation planning, user training, and ongoing maintenance, this MIS offers a sustainable solution that can serve as a model for vocational schools across Indonesia, showcasing the potential of digital solutions in advancing educational administration and supporting career readiness in vocational education.